Miracle - Steel, Danielle (London : Corgi Books, 2006)
It is New Year's Eve when the storm of the century hits northern California. For Quinn Thompson, what happens in the storm's wake will bring down a barrier he has built around himself since his wife's death. For neighbor Maggie Dartman, it will spark friendship at a time when she needs it most.
Keywords: Loss (Psychology) -- Fiction; Psychological fiction; Love stories